Efficacy of common salvage chemotherapy regimens in patients with refractory or relapsed acute myeloid leukemia: A retrospective cohort study. Issue 39 (September 2018) - Xu, Jun; Lv, Ting-Ting; Zhou, Xiao-Fen; Huang, Ying; Liu, Dong-Dong; Yuan, Guo-Lin
Abstract : Abstract: To assess treatment response and overall survival (OS) in refractory or relapsed acute myeloid leukemia (R/R AML) patients treated by different common salvage chemotherapy regimens. Medical records data from 142 R/R AML patients were reviewed in this retrospective study. Patients were treated with regimens based on the following drugs: cytarabine, granulocyte colony-stimulating factor (G-CSF), and fludarabine (FLAG) (n = 46); cytarabine and G-CSF in addition to aclarubicin or daunorubicin (CAG/DAG) (n = 30); cytarabine, G-CSF, and cladribine (CLAG) (n = 27); cytarabine, etoposide, and mitoxantrone (MEA) (n = 17); cytarabine plus idarubicin, daunorubicin, or mitoxantrone (IA/DA/MA) (n = 12); and homoharringtonine, cytarabine, and aclarubicin or daunorubicin (HAA/HAD) (n = 10). A total of 43 (35.2%) patients achieved complete remission (CR), 60 (49.2%) patients achieved overall remission rate (ORR), and 18 (14.8%) patients received allogeneic hematopoietic stem cell transplantation (allo-HSCT) after CR. Median OS was 8.0 (95% CI 6.6–9.4) months with a 1-year OS rate of (29.9 ± 3.9)% and 3-year OS rate of (11.1 ± 3.6)%. No difference of CR ( P  = .621), ORR ( P  = .385), and allo-HSCT ( P  = .537) achievement was observed among different chemotherapy regimens. Interestingly, we observed that the CLAG-based regimen did not affect CR ( P  = .165), while it achieved a numerically higher ORR ( P  = .093) and was an independent factor for prolonged OS ( P  = .016). No other regimens were determined to be correlated with CR, ORR, or OS. FLAG-, CAG/DAG-, CLAG-, MEA-, IA/DA/MA- and HAA/HAD-based regimens were found to achieve similar CR rates, while the CLAG-based regimen achieved numerically higher ORR rates and significant favorable OS. Therefore, CLAG-based regimens should be a prioritized treatment option for R/R AML patients. Abstract : Supplemental Digital Content is available in the text